PENGARUH MACAM AUKSIN PADA PEMBIBITAN BEBERAPA VARIETAS TANAMAN JATI (Tectona grandis, L.) - Didi Kuntoro; Rahayu Sarwitri; Agus Suprapto (Universitas Tidar, 2016)
An experiment about of the effect auxin kind on growth of seedling of teak varieties (Tectona grandis, L.) had been done since February 15, 2016 until May 7, 2016 in Field Station on Seed Development Center and Pilot Forestry Yogyakarta at Bunder Village, Playen District, Gunung Kidul Regency, Yogyakarta which the type of soil latosol, pH 6,8 and an altitude is 160 m above sea level. The method of experiment is factorial (4x3) with randomized completely block design and three replications. The first factor is kind of auxin; there are four levels: control, IAA, IBA, NAA. The second factor is kind of varieties, there are three levels: Thailand (Siam), Cepu (Supergama) and Wanagama (Utama) variety. The result of analysis show that the uses of IBA may increases of shoot height; fresh and dry weight of shoot, root length, also fresh and dry weight of root. Cepu variety (Supergama) show the higher shoot and heaviest fresh weight of shoot. There were no efect between kind of auxin and varieties at all parameters.